Analysis of Detecting Potential Financial Statement Fraud in State-Owned Enterprises (SOEs) Using the Fraud Hexagon - Rasyidah, Rasyidah; Anwar, Azwar; Hamzah, Hajrah (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2024)
This study aims to analyze the effect of elements in the Fraud Hexagon on financial statement fraud in state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The dependent variable in this study is financial statement fraud, measured by the F-score Model. The independent variables are the six elements in the fraud hexagon: pressure, opportunity, rationalization, capability, arrogance, and collusion, each proxied by performance level, monitoring ineffectiveness, change of auditors, change of director, CEO duality, and audit fees. This study utilizes 105 sample data selected using the purposive sampling method. The data was analyzed using multiple linear regression analysis. The results indicate that pressure (performance level) has a positive and significant effect on financial statement fraud. Capability (change of director) has a negative and significant effect, suggesting that changes in leadership can mitigate fraud risks. However, opportunity (monitoring ineffectiveness), rationalization (change of auditors), arrogance (CEO duality), and collusion (audit fees) do not significantly influence the potential for financial statement fraud. These findings highlight the importance of monitoring performance levels and leadership changes in preventing financial statement fraud in SOEs. The study provides valuable insights for regulators and corporate governance bodies to enhance their fraud prevention frameworks and ensure the integrity of financial reporting. This research contributes to the existing literature by integrating the Fraud Hexagon model in the context of SOEs, offering a comprehensive understanding of the factors influencing financial statement fraud in a developing country.